The AirSR two-component system contributes to Staphylococcus aureus survival in human blood and transcriptionally regulates sspABC operon - Hall, Jeffrey W.; Yang, Junshu; Guo, Haiyong; Ji, Yinduo (Frontiers in Microbiology, 2015)
To date, genes identified and transcriptionally regulated by the AirSR TCS have been involved in energy production and cellular homeostasis of the staphylococcal cell. It is well accepted that the state of cellular metabolism impacts the expression of virulence factors in Staphylococcus aureus. For this reason, we conducted experiments to determine if the AirSR TCS contributes to the pathogenesis of S. aureus using an antisense RNA interference technology, an inducible overexpression system, and gene deletions. Depletion of AirSR by antisense RNA expression or deletion of the genes, results in significant decrease in bacterial survival in human blood. Conversely, overexpression of AirR significantly promotes survival of S. aureus in blood. AirR promotes the secretion of virulence factors that inhibits opsonin-based phagocytosis. This enhanced survival is partially linked to the direct transcriptional regulation of the sspABC operon, encoding V8 protease (SspA), staphopain B (SspB) and staphostatin B (SspC). SspA and SspB are known virulence factors which proteolytically digest opsonins and inhibit killing of S. aureus by professional phagocytes. This is the first evidence linking the AirSR TCS to pathogenesis of S. aureus.